2021
DOI: 10.3390/ijerph182010608
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Extremity Functional Index: Reliability and Validity in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The aim of the current study was to examine the psychometric properties of the upper extremity functional index (UEFI) in patients with chronic obstructive pulmonary disease (COPD). Seventy patients with stable COPD completed the UEFI and St. George Respiratory Questionnaire (SGRQ) and performed lung function tests in the first testing session. They completed the UEFI and the Global Rating of Change Scale in the second session, which was within ten days of the first session. The UEFI floor and ceiling effects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The overall score for the UEFI ranges from 0 (reflecting the worst upper extremity function) to 80 (indicating the best upper extremity function). Previous research studies have established the construct validity, reliability, and responsiveness of the Arabic version of the UEFI utilized in the current study in patients with upper extremity musculoskeletal disorders (Aljathlani et al, 2022;Alnahdi, 2023).…”
Section: Uefimentioning
confidence: 99%
See 1 more Smart Citation
“…The overall score for the UEFI ranges from 0 (reflecting the worst upper extremity function) to 80 (indicating the best upper extremity function). Previous research studies have established the construct validity, reliability, and responsiveness of the Arabic version of the UEFI utilized in the current study in patients with upper extremity musculoskeletal disorders (Aljathlani et al, 2022;Alnahdi, 2023).…”
Section: Uefimentioning
confidence: 99%
“…The adapted Arabic UEFI was simple and understandable to Arabic-speaking patients with upper extremity musculoskeletal disorders. Prior studies have examined the measurement properties of the Arabic UEFI in individuals with upper extremity musculoskeletal disorders and also in individuals with chronic obstructive pulmonary disease (Alnahdi and Albarrati, 2021;Aljathlani et al, 2022;Alnahdi, 2023). These prior reports suggested that the Arabic UEFI has excellent internal consistency with homogenous items, test-retest reliability, reasonable measurement error, and substantiating evidence for its construct validity and responsiveness as a tool for assessing upper extremity function.…”
Section: Introductionmentioning
confidence: 99%
“…The UEFI has been adapted into the Arabic language and its measurement properties were tested in patients with upper extremity musculoskeletal disorders and also in patients with chronic obstructive pulmonary disease [13,14]. The Arabic UEFI demonstrated excellent internal consistency, test-retest reliability, an acceptable measurement error and evidence supporting its validity as a measure of upper extremity function [13,14].…”
Section: Introductionmentioning
confidence: 99%